Extracellular vesicles engineered to bind albumin demonstrate extended circulation time and lymph node accumulation in mouse models. Issue 7 (25th July 2022) - Liang, Xiuming; Niu, Zheyu; Galli, Valentina; Howe, Nathalie; Zhao, Ying; Wiklander, Oscar P. B.; Zheng, Wenyi; Wiklander, Rim Jawad; Corso, Giulia; Davies, Christopher; Hean, Justin; Kyriakopoulou, Eleni; et al.
Abstract: Extracellular vesicles (EVs) have shown promise as potential therapeutics for the treatment of various diseases. However, their rapid clearance after administration could be a limitation in certain therapeutic settings. To solve this, an engineering strategy is employed to decorate albumin onto the surface of the EVs through surface display of albumin binding domains (ABDs). ABDs were either included in the extracellular loops of select EV‐enriched tetraspanins (CD63, CD9 and CD81) or directly fused to the extracellular terminal of single transmembrane EV‐sorting domains, such as Lamp2B. These engineered EVs exert robust binding capacity to human serum albumins (HSA) in vitro and mouse serum albumins (MSA) after injection in mice. By binding to MSA, circulating time of EVs dramatically increases after different routes of injection in different strains of mice. Moreover, these engineered EVs show considerable lymph node (LN) and solid tumour accumulation, which can be utilized when using EVs for immunomodulation, cancer‐ and/or immunotherapy. The increased circulation time of EVs may also be important when combined with tissue‐specific targeting ligands and could provide significant benefit for their therapeutic use in a variety of disease indications. Abstract :